miR-548d-3p Is Up-Regulated in Human Visceral Leishmaniasis and Suppresses Parasite Growth in Macrophages - Ramos-Sanchez, Eduardo Milton; Reis, Luiza Campos; Souza, Marina de Assis; Muxel, Sandra Márcia; Santos, Kamila Reis; Lagos, Dimitris; Pereira, Valéria Rêgo Alves; Brito, Maria Edileuza Felinto de; Kaye, Paul Martin; Floeter-Winter, Lucile Maria; Goto, Hiro (Frontiers in Cellular and Infection Microbiology, 2022)
Visceral leishmaniasis caused by Leishmania (Leishmania) infantum in Latin America progress with hepatosplenomegaly, pancytopenia, hypergammaglobulinemia, and weight loss and maybe lethal mainly in untreated cases. miRNAs are important regulators of immune and inflammatory gene expression, but their mechanisms of action and their relationship to pathogenesis in leishmaniasis are not well understood. In the present study, we sought to quantify changes in miRNAs associated with immune and inflammatory pathways using the L. (L.) infantum promastigote infected- human monocytic THP-1 cell model and plasma from patients with visceral leishmaniasis. We identified differentially expressed miRNAs in infected THP-1 cells compared with non-infected cells using qPCR arrays. These miRNAs were submitted to in silico analysis, revealing targets within functional pathways associated with TGF-β, chemokines, glucose metabolism, inflammation, apoptosis, and cell signaling. In parallel, we identified differentially expressed miRNAs in active visceral leishmaniasis patient plasma compared with endemic healthy controls. In silico analysis of these data indicated different predicted targets within the TGF-β, TLR4, IGF-I, chemokine, and HIF1 pathways. Only a small number of miRNAs were commonly identified in these two datasets, notably with miR-548d-3p being up-regulated in both conditions. To evaluate the potential biological role of miR-548d-3p, we transiently transfected a miR-548d-3p inhibitor into L. (L.) infantum infected-THP-1 cells, finding that inhibition of miR-548d-3p enhanced parasite growth, likely mediated through reduced levels of MCP-1/CCL2 and nitric oxide production. Further work will be required to determine how miR-548d-3p plays a role in vivo and whether it serves as a potential biomarker of progressive leishmaniasis.